NEED FOR MULTI-AGENT SYSTEM IN SMART GRIDS - M.Sivaram Krishnan, Viyathukattuva M.A.M.M (International Journal of Advanced Science and Technology, 2020)
As renewable energy-based generations are increasing in the distribution networks, new technical challenges are increasing. In the case of solar PV generations, the proximity of connected inverters and diversity factors of solar PV inverters increase the probability of overvoltage problem. Similarly, the diversity factor of solar PV inverters increases the possibility of reverse power flow as well. These problems could drive the distribution system operators to restrict additional integration of solar PV inverters in their distribution networks. Nevertheless, these problems can be addressed by controlling the inverters via a dedicated control scheme, like supervisory control and data acquisition. However, while considering the number of smart devices that will be connected to the low voltage networks, the cost of implementing SCADA like scheme will be very high. Alternatively, information and communication paradigm, such as multi-agent system can be utilized to address theaforementioned technical challenges. The multi-agent system can accommodate different control approaches, such as decentralized control or hierarchical control, which can be utilised to mitigate the technical challenges.